Application of Restorative Justice in Handling Persecution - Rosa, Qobitin Elia (Police Studies Review, 2024)
When we talk about handling abuse cases, the approach taken is often through a punitive legal system. However, more and more countries and communities are starting to look at alternative approaches that are more humane and deeper: restorative justice. Restorative justice offers an approach that focuses on healing, reconciliation, and rebuilding communities affected by criminal acts, including abuse. In this article, we will explore the concept of restorative justice and how this approach can be applied in handling cases of abuse.